The prevalence of antibodies to Toxoplasma gondii in sheep in the Western Cape, South Africa - Hammond-Aryee, Kenneth (Onderstepoort J Vet Res, 2015)
The seroprevalence of Toxoplasma gondii antibodies in a sample of 292 merino sheep farmed in a semi-intensive manner in the Overberg region of the Western Cape, South Africa, was investigated. Antibody seroprevalence was determined by enzyme-linked immunosorbent assay. Of the total sample, 23 sheep tested positive for T. gondii antibodies (8%; 95% CI: 4.7688–10.9846). There was no statistically significant relationship between seroprevalence and age of the sheep. The highest seroprevalence was found in sheep between 28 and 40 months old; a total of 19 sheep were seropositive by 40 months. No seropositive sheep were found in the age group between 16 and 28 months. The seroprevalence reported in this study is higher than what has previously been reported for the Western Cape (6%) and across South Africa on average (4.7%). As sheep farming is economically significant in South Africa, the presence of T. gondii amongst sheep may pose a production threat to the small-stock industry as well as to public health and food security. We therefore recommend further surveillance to identify high-risk animal populations so that local control measures can be put in place.